A conceptual framework for accountability of the airport industry in the transition from ex-ante regulation to ex-post regulation. (December 2020) - Giovanelli, Lucia; Rotondo, Federico
Abstract: Regulation of companies with market power in the provision of the essential services has been intended to provide incentives aimed at improving efficiency and service quality. Few studies have investigated the accountability of regulated industries and answered the question of the most appropriate accounting model for protecting consumers, promoting competition and ensuring investors' profitability. With the transition from an ex-ante to an ex-post model – based on free negotiation between stakeholders on price setting and monitoring activity by an independent authority – in many settings, the effectiveness of the accounting model seems to be strictly related to the quantity and quality of the information that regulated companies provide on a mandatory basis in anticipation of consultations with service users, and the quantity and quality of information that they voluntarily offer to stakeholders via their financial reporting. This paper aims to explore accountability relationships that emerge in regulated airport industries moving from ex-ante to ex-post models in order to propose a conceptual framework capable of remedying the shortcomings of the extant ones and, in particular, the conceptual framework established by Vass (1992) . The new framework is also used to identify which accounting model is required to improve the effectiveness of regulation. Highlights: Accountability relationships in ex-post regulated airport industries are explored. Divided accounting is no more appropriate for all stakeholders' information needs. A conceptual framework is proposed to interpret new accountability relationships. The accounting model should be revised to improve regulation effectiveness. Some solutions are outlined to secure the accountability of regulated airports.